Home recording technique training for the pare strings ensemble community - East Java - Anggoro, Raden Roro Maha Kalyana Mitta; Karyawanto, Harpang Yudha; Murbiyantoro, Heri; Dharmawanputra, Budi; Mahendra, Marda Putra (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2023)
College may be a logical institution that has the most assignment of carrying out the Tri Dharma of College, specifically instruction and instructing, research, and community service. Through the assignments it carries out, it is trusted that university educate will gotten to be centers of total human advancement as well as upkeep and advancement of science, innovation and arts in understanding with current and future needs. As with other Art Colleges in Indonesia, the Music Study Program, Faculty of Languages ​​and Arts, Universitas Negeri Surabaya, in arrange to execute the Tri Dharma of College and “One Step Ahead” endeavours, different exercises were carried out which were showed within the frame of "Home Recording Training In the Pare String Ensemble Music Group Community in Kediri”. This training points to present and execute advanced proficiency within the domain of Music Expressions, to be specific with respect to music generation utilizing DAW or Studio One software. This DAW can afterward ended up the most arrangement for each person part of the Pare String Gathering to create a collection that's prepared, increment polished skill in work (particularly in working the Music Learning Management System). This action can make a positive commitment to musician or music specialists in confronting the challenges of the worldwide music industry, by optimally maximizing the potential of human assets and taking after current mechanical improvements, so that they can compete within the entertainment industry advertise, particularly within the East Java locale, as well opening job opportunities and economic improvement for artists.